STRATEGI PENGGUNAAN JENIS PESAWAT DALAM MENGHADAPI PERSAINGAN - CHARLES An (Institut Transportasi dan Logistik Trisakti, 2015)
Increasing competition in the airline industry sectors make each airline must implement effective and efficient strategies to determine type of aircraft which is more economical to save operating costs and ticket prices or rates that can compete with its competitors. It has been done by PT. Sriwijaya Air. Through management strategic methods and SWOT analysis, despite the increasing of crude oil prices today which affect the air transport cost, PT. Sriwijaya Air, as one of the air transportation services provider, should make initiative decision to improve yield, revenue and profit to maintain the sustainability of the company.